Delivery of Short Hairpin RNA Sequences by Using a Replication-Competent Avian Retroviral Vector - Bromberg-White, Jennifer L. (American Society for Microbiology, 2004)
While recent studies have demonstrated that retroviral vectors can be used to stably express short hairpin RNA (shRNA) to inhibit gene expression, these studies have utilized replication-defective retroviruses. We describe the creation of a replication-competent, Gateway-compatible retroviral vector capable of expressing shRNA that inhibits the expression of specific genes.